Materiais híbridos magnético-luminescentes envolvendo complexos de íons lantanídeos - Pires, Gilvan Pozzobon (2016)
The present study develops bifunctional optical magnetic materials with high lantanide content. For this purpose, magnetite was pepared by co-precipitation method and chelating groups were introduced on the Fe3O4 surface with organosilanes containing ethylenediaminetetraacetic acid (EDTA) derivative, which were previously prepared via reaction between EDTA-dianhydride and aminoalkyl alkoxysilanes agents: 3- (Trimethoxysilyl)propylamine (1N), N-[3(trimethoxysilyl)propyl] ethylenediamine (2N) and N1-(3-trimethoxysilylpropyl)diethylenetriamine) (3N). After coordination of lanthanide ions (Gd3+, Eu3+, Tb3+ or Sm3+), the first coordination sphere of the lanthanide ions in the Ln-EDTA complexes, present on the modified surfaces of Fe3O4 particles, were completed by addition of -diketonate ligands (tta: thenoyltrifluoroacetonate, dbm: dibenzoylmetane, bzac: benzoylacetone and acac: acetylacetone) in order to improve their luminescence properties. The materials were characterized by powder X-ray diffraction (XRD), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), wavelength dispersive X-ray fluorescence (WDXRF) and Fourrier-transform infrared spectroscopy (FT-IR) as well as by zeta potential measurements and luminescence spectroscopy. The hybrid materials exhibited intense red emission assigned to the 4f-4f transitions of the Eu3+ ion, likewise characteristic green and orange emissions of Tb3+ and Sm3+, respectively, indicating an efficient intramolecular ligand-to-metal energy transfer. The experimental intensity parameters ( 2 and 4), lifetimes (t), as well as radiative (Arad) and non-radiative (Anrad) decay rates of the Eu3+ ion were determined and discussed.